Growth hormone deficiency and cardiovascular risk. - Hew, F.L.; O'Neal, D.; Kamarudin, N.; Alford, F.P.; Best, J.D. (1998)
It is now recognized that growth hormone (GH) deficiency in adults represents a distinct clinical syndrome that encompasses reduced psychological well-being as well as specific metabolic abnormalities. The latter features, which include hypertension, central obesity, insulin resistance, dyslipidaemia and coagulopathy, closely resemble those of metabolic insulin resistance syndrome. The increased cardiovascular morbidity and mortality demonstrated in these GH-deficient (GHD) adults reinforce the close association between the two syndromes. Replacement of GH in GHD adults has resulted in a marked reduction of central obesity and significant reduction in total cholesterol but little change in other risk factors, in particular insulin resistance and dyslipidaemia. The persistent insulin resistance and dyslipidaemia, together with the elevation of plasma insulin levels and lipoprotein (a) with GH replacement in these subjects are of concern. Long-term follow-up data are required to assess the impact of GH replacement on the cardiovascular morbidity and mortality of GHD adults. Further exploration of the appropriateness of the GH dosage regimens currently being employed is also indicated.